Oncogenic human papillomavirus genital infection in southern Iranian women: population-based study versus clinic-based data - Eghbali, S.S.; Amirinejad, R.; Obeidi, N.; Mosadeghzadeh, S.; Vahdat, K.; Azizi, F.; Pazoki, R.; Sanjdideh, Z.; Amiri, Z.; Nabipour, I.; Zandi, K. (2012)
Background: Epidemiological studies on genital human papilloma viruses infection (HPVs) in general population are crucial for the implementation of health policy guidelines for developing the strategies to prevent the primary and secondary cervical cancer. In different parts of Iran, there is a lack of population-based studies to determine the prevalence of HPV in the general population. The aim of this population-based study is to compare the prevalence rate of genital HPV infection among reproductive women with our previous clinic-based data, which showed a prevalence rate of 5 in women in southern Iran. Results: Using general primers for all genotypes of HPV, of 799 randomly selected women, five (0.63, 95 CI 0.23-1.55) tested positive for HPV DNA. Overall, seven different HPV genotypes were detected: six types (16, 18, 31, 33, 51 and 56) were carcinogenic, or "high risk genotypes" and one genotype (HPV-66) was "probably carcinogenic." Conclusions: In a population-based study, the prevalence of HPV infection among southern Iranian women was lower than that observed worldwide. However, our gynaecological clinic-based study on the prevalence of HPV infection showed results comparable with other studies in the Middle East and Persian Gulf countries. Since gynaecological clinic-based data may generally overestimate HPV prevalence, estimates of prevalence according to clinic-based data should be adjusted downward by the population-based survey estimates.